The Effect of Supplementation with Some Essential Oils on the Mobility and the Vitality of Human Sperm - Modou M. Mbaye; Bouchra El Khalfi; Boutaina Addoum; Papa D. Mar; Brahim Saadani; Noureddine Louanjli; Abdelaziz Soukri (The Scientific World Journal)
The objective of this work is to study the improvement effect of some essential oils of sage (Salvia officinalis), oregano (Origanum vulgare), and eucalyptus (eucalyptus globulus) on the physiological parameters characterizing the quality of human sperm (mobility and vitality). We find natural biomolecules to improve sperm quality to increase the chances of success of very low in vitro fertilization (IVF) that stagnate around 20%. Sperm samples were mixed with different concentrations of essential oils. The effect of these essential oils on the motility and vitality of spermatozoa has been analyzed. The mobility was determined using a Computer Assisted Sperm Analysis (CASA). In the other side, the evaluation of sperm vitality was performed by staining eosin 2% and the microscopic examination is carried out via optical microscope. A drop of sperm will be mixed with a drop of eosin solution 2%, spread between the slip and coverslip, then allowed to air dry, and examined under a microscope. A significant improvement in the mobility and vitality of human spermatozoa has been noted with oregano. Eucalyptus after 10 min of exposure also significantly improves the mobility and vitality of the spermatozoa. Sage does not improve mobility for these incubation times but significantly improves vitality.